Integrating interpersonal space and shared workspace for translation groupware development - Lim, T.K; Tang, E.K.; Wong, C.Y.; Woods, P.; Yeo, Alvin Wee; Chen, Chwen Jen (2009)
Translation is a process that allows people to learn and comprehend others' ideas or cultures in their own language. A translation groupware, that allows two or more human translators to edit the output of machine translation at different times and different places, is developed in order to overcome the limitation of human translators and machine translation. However, translation groupware still not widely adopted by current human translators and the effectiveness is not known. An understanding of how multiple translators work and interact within a group is vital to develop a usable groupware. It is hypothesized that collaborative awareness can improve the translation groupware usability. Collaborative awareness components, such as interpersonal space and shared workspace, are identified as important characteristics to enhance the usability of translation groupware.